Maternal risk factors associated with premature birth in adolescent pregnant treated at the National Hospital Dos de Mayo from 2018 to 2019, Lima – Peru - Murguia-Ricalde, Frankchesca N. (2021)
INTRODUCTION: The most frequent cause of preterm birth is idiopathic; however, there are various risk factors that could trigger it, which with early diagnosis and timely management could reduce neonatal morbidity and mortality and subsequent sequelae. OBJECTIVE: To determine the maternal risk factors that predispose to premature birth in pregnant adolescents treated at the Hospital Nacional Dos de Mayo, during the period 2018 - 2019. MATERIALS AND METHODS: Analytical, observational, retrospective, case-control study. 180 pregnant women aged 10-19 years were studied, divided into 60 cases and 120 controls. The information from the medical records was compiled using a data collection form, ensuring that the inclusion and exclusion criteria were met. The results were adjusted using a multivariate binary logistic regression model. RESULTS: The average maternal age was 17.49 years, 71.7% of pregnant women were in late adolescence (17-19 years). According to the multivariate analysis, the variables: anemia (OR: 2.074; 95% CI = 1.075 - 4.001; p = 0.030), urinary tract infection (OR: 3.863; 95% CI = 1.508 - 9.896; p = 0.005) and preeclampsia (OR: 3.714; 95% CI = 1.122 - 12.301; p = 0.032), were associated with an increased risk of preterm birth; While no statistically significant association was found with vaginal infection (OR: 2.111; 95% CI = 0.651 - 6.850; p = 0.205) and premature rupture of membranes (OR: 1.267; 95% CI = 0.609 - 2.633; p = 0.526 ). CONCLUSIONS: In our study, the variables associated with an increased risk of preterm birth in pregnant adolescents were anemia, urinary tract infection and preeclampsia.